Organoid technology in female reproductive biomedicine - Heidari-Khoei, Heidar (Reprod Biol Endocrinol, 2020)
Recent developments in organoid technology are revolutionizing our knowledge about the biology, physiology, and function of various organs. Female reproductive biology and medicine also benefit from this technology. Organoids recapitulate features of different reproductive organs including the uterus, fallopian tubes, and ovaries, as well as trophoblasts. The genetic stability of organoids and long-lasting commitment to their tissue of origin during long-term culture makes them attractive substitutes for animal and in vitro models. Despite current limitations, organoids offer a promising platform to address fundamental questions regarding the reproductive system’s physiology and pathology. They provide a human source to harness stem cells for regenerative medicine, heal damaged epithelia in specific diseases, and study biological processes in healthy and pathological conditions. The combination of male and female reproductive organoids with other technologies, such as microfluidics technology, would enable scientists to create a multi-organoid-on-a-chip platform for the next step to human-on-a-chip platforms for clinical applications, drug discovery, and toxicology studies. The present review discusses recent advances in producing organoid models of reproductive organs and highlights their applications, as well as technical challenges and future directions.